Cosmetic intervention among Iraqi women, prevalence and associated factors (demographic, place, and time) - Riyadh Khudhair Lafta,; Israa Abdulghafoor Kareem, (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the prevalence of cosmetic interventions, and the factors that instigate women to undergo such procedures. Method: The cross-sectional study was conducted from January to June 2021 in Baghdad, Iraq, and comprised women aged 18 years or above from 4 general hospitals, 4 health centres and 8 schools. The sample was divided into group A having subjects with experience of cosmetic interventions, and group B having those with no such exposure. Data was collected using a a questionnaire. Data was analysed using SPSS (version 25). Results: Of 1113 women, 997(90%) were aged 20-40 years. There were 375(34%) women in group A and 738(66%) in group B. Within group A, Botox was the most common intervention 89(23%). Besides, 215(57%) women had the intervention in clinics, and 75(20%) had it in beauty centres. Dermatologist did the intervention in 146(39%) cases, while side effects were noted in 142(38%). Within group A, 248(66%) subjects said they would not advise their daughters or sisters to have cosmetic interventions. Age and marital status were significantly different between the study groups (p<0.05). Conclusion: Cosmetic interventions among the women studied were found to be relatively high, and Botox was the most common intervention. Key Words: Botulinum Toxins, Dermatologists, Nuclear,